Invenções cartográficas uma poética da criação... imagens cotidianas - Giovanella, Alessandra (2007)
The actual research, accomplished in the Teaching Post-Graduation Course, Arts Education field, results from the activities realized from 2001 to 2003 at the school of incomplete fundamental education Intendente Manuel Ribas, sited at Caturrita village, in Santa Maria, RS, in which there has not been a practice regarding Art Education. The subjects of this investigation are students from the 2nd, 3rd and 4th year. The village is stigmatized and known as Dump , due to the fact that the waste disposal of the city is located in that area and most of its workers get their income out of that in subhuman conditions, without any protection, having low financial support and under exploration circumstances imposed by the companies that negotiate the product of their work . The applied methodology aims to cartograph their meetings and the affections produced by the dialogs of the praxis; the approach is qualitative; the instruments used for gathering data are direct and participative observation, analyses of the creation process, field journal and semi-structured interviews. The research has as objectives to investigate how the creative process is developed by the subjects and to what extent the development of visual language potentializes the construction of subjectivities in relation to the vivential quotidian and the social context in order to offer possibilities for a potentially active, common doing. Thinking the outside of the school and itself as inserted in the context and system, the experiments lived through the creative action proportionated the cognitive development and were converted into sense production, autonomy, initiative, flexibility, sensibility, and self-confidence, without producing an universal identity molded according to educational practices that try to frame everyone into an asepsis controlled by rules of submission